Development of Chemical Resistant Geopolymer As Waste Storage Containing Hazardous Material - Md Mustfa, Mohamad Khairulanuar (Universiti Teknologi PETRONAS, 2013)
This research paper is to develop a geopolymer as as waste storage containing radioactive material. This topic is very relevant to our current world as there is still no certain solution for the storage for the radioactive material. The rate at which other environmental problems are mounting is also alarming. The toxic dumps are filled at a rapid pace, with few sites being developed. Abandoned mining waste laden with heavy metals and acidic solutions are poisoning vast acres of once-virgin land. The world water quality is worsening and our river and sea are being contaminated with this chemical wastes. In order to fulfill the objective of this research in which to develop a sustainable radioactive waste container by using geopolymer material, number of tests and experiments need to be conducted. The tests that are need to undergone are water absorption test, sulfuric acid test on geopolymer, and also sodium sulfate test on geopolymer. The main purpose of these tests is to determine the best properties out from the geopolymer to be applied as waste storage. The length of this research is up to six months starting from March 2013 until September 2013.